PENGARUH PENGUNGKAPAN SUKARELA MANAJEMEN RISIKO TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Property, Real Estate, dan Building Construction yang Terdaftar pada Bursa Efek Indonesia periode 2017) - Henrikus Balzano Anggoro Seto; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of voluntary disclosure of risk management on firm value in Property, Real Estate, and Building Construction Comspanies Listed on the Indonesia Stock Exchange in 2017 period In addition, this study also examines whether the presence of broader disclosures from companies can reduce asymmetry information with users of information that is very necessary for making decisions. On the basis of signal theory, which is about information asymmetry, companies that have more information should have high corporate values.The population in this study are Property, Real Estate, and Building Construction companies that are listed on the Indonesia Stock Exchange in the 2017 period. Finally, there were 51 samples from 69 populations listed on the IDX. The analytical tool used in this study is multiple regression analysis.The test results show that the disclosure of operational risk, strategy risk, and integrity risk has a positive and significant effect on firm value while empowerment risk and information and technology processing risks that do not affect the firm's value. With these results it can be said that more disclosure from a company will increase the value of the company in the eyes of investors, the non-influential disclosure of empowerment risk may be influenced by several other factors.